Executive Committee Minutes 2018-09-20 - Academic Senate:::::::::
Agenda Approved. Minutes of 9/6/18 Approved. Chair Report. Provost Report. Minimal Adjustments to Program: (ELSE Department) Credential Program, Preliminary Education Specialist approved for the Senate consent calendar. From S&F: Proposed By-Law Change – Times and Days of faculty governance committees – approved as a business item for the Senate agenda. Vice Chair Report. Vice President of Administration and Finance Report. APARC Report. EPC Report. FSAC Report. Associate Students Report. Senate agenda approved.